Avaliação da erosão hídrica, transporte de sedimentos e qualidade da água na bacia do córrego Monjolo Grande - Couto Júnior, Antonio Aparecido [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Understanding the linkages between the natural elements is essential for being promoted the land use, occupation and sustainable management of environmental systems. Universal Soil Loss Equation (USLE), as a predictive model of erosion, is important to allowing the prevention of possible environmental impacts which may drastically interfere in natural or anthropic environments, as well as prevent potential financial wastes and even contribute to greater efficiency of agricultural production. This research will be working some USLE parameters, emphasizing topographic factor from Ribeirão Monjolo Grande watershed. Among the factors considered by the USLE, the Topographic Factor interferes directly in the erosive dynamic of a watershed because it involves variables related to hydrological processes that occur on it. In this research, were discussed different methods for obtaining the Topographic Factor (BERTONI e LOMBARDI NETO, 1985; MOORE e BURCH, 1986; DESMET E GOVERS, 1996) in GIS environment. After comparison between the methods, was indicated that best represents the conditions of geometry strand of the study area. Finally, other factors (R, K, C, P) considered by the USLE were obtained. The attainment of these parameters were guided by the use of geotechnologies, especially in Geographic Information Systems (GIS), with the assistance of secondary data and periodic field visits. The results obtained contributed to the understanding of hydrosedimentological dynamic in this area and serve as a viable strategy for studies of soil loss, aiming at developing consistent material for future researches about environmental planning and land management

A compreensão das relações existentes entre os elementos naturais é fundamental para que possa ser promovido o ordenamento de uso, ocupação e gestão sustentável dos sistemas ambientais. Nesse contexto, a Equação Universal de Perda de Solo (EUPS), como um modelo preditivo à erosão, é importante por possibilitar a prevenção de impactos ambientais que possam interferir drasticamente em ambientes naturais ou antrópicos, bem como evitar possíveis investimentos equivocados e até mesmo contribuir para maior eficiência da produção agrícola. Dentre os fatores contemplados pela EUPS, o Fator Topográfico (LS) interfere diretamente na dinâmica erosiva de uma bacia hidrográfica, pois envolve variáveis relacionadas aos processos hidrológicos que nela ocorrem. Nesse estudo foram abordados diferentes métodos existentes para a obtenção do Fator Topográfico (BERTONI e LOMBARDI NETO, 1985; MOORE e BURCH, 1986; DESMET E GOVERS, 1996) em ambiente SIG. Após a comparação entre os métodos, indicou-se aquele que melhor representa as condições de geometria de vertente da área em estudo. Por fim, foram obtidos outros fatores (R, K, C e P) contemplados pela EUPS. A obtenção desses parâmetros pautou-se na utilização de geotecnologias, sobretudo em Sistemas de Informação Geográfica (SIG), com o auxílio de dados secundários e visitas periódicas a campo. Os resultados obtidos contribuíram para o entendimento da dinâmica hidrossedimentológica da área de interesse e servem como uma estratégia viável para estudos de perda de solo, dando suporte a elaboração de material consistente como subsídio a uma abordagem de planejamento ambiental e gestão territorial
Keywords: Erosão; Água - Qualidade; Sistemas de informação geografica; Sedimentos fluviais; Geotecnologia ambiental; Monjolo Grande, Ribeirão, Ipeúna (SP)